Local Economic Growth and Infant Mortality - Andreas Kammerlander; Günther G. Schulze (Center for Economic Studies and ifo Institute (CESifo), 2021)
We show, for the first time, a causal effect of local economic growth on infant mortality. We use geo-referenced data for non-migrating mothers from 46 developing countries and 128 DHS survey rounds and combine it with nighttime luminosity data at a granular level. Using mother fixed effects we show that an increase in local economic activity significantly reduces the probability that the same mother loses a further child before its first birthday.
Keywords: I15; O18; 330; local economic growth; child mortality; nighttime lights